Meningkatkan Kesadaran Lingkungan Melalui Sosialisasi 3R (Reduse, Reuse, Recycle): Praktik Nyata di Bank Sampah PangGold - Luki Oka Prastio; Laeli Nur Khanifah; Anistya Vinta Desi (Komunitas : Jurnal Pengabdian Kepada Masyarakat, 2026)
The community service program at Bank Sampah PangGold Cilegon aimed to increase public awareness and participation through the implementation of the 3R principles (Reduce, Reuse, Recycle). Activities were carried out through socialization, training, mentoring, and the use of appropriate technologies such as plastic shredding machines, pressing machines, and Black Soldier Fly (BSF) maggot cultivation. Waste management remains a major issue in Indonesia, particularly due to the low level of public awareness in waste sorting and reuse. As a result of the program, community participation increased from 15 to more than 50 households. Bank Sampah PangGold also succeeded in establishing an organizational structure based on TPS3R Plus and enhancing production capacity through the processing of both plastic and organic waste. This program not only encouraged behavioral change among the community but also created new economic opportunities while strengthening the role of the waste bank as a community-based integrated waste management center.